Dynamic beam control based on electrically switchable nanogratings from conducting polymers - Lee Yohan; Karst Julian; Ubl Monika; Hentschel Mario; Giessen Harald (Nanophotonics)
Surging interests in point-of-device miniaturization have led to the development of metasurface-based optical components. Here, we demonstrate an electrically-driven ultracompact beam controller in the infrared spectral range. The effect benefits from diffraction gratings consisting of the commercially available conductive polymer PEDOT:PSS, which exhibits metal-to-insulator transition characteristics upon electrical biasing. By combining several metagratings with different superlattice periods in electrically isolated areas, our device enables diffraction beams at 16 and 33.5° when applying voltages of only ±1 V. Furthermore, no diffraction is realized by switching off the plasmonic property of the gratings. Dynamic control of electromagnetic wave via the presented platforms could be transformative for sensing, imaging, and communication applications.